Flavopiridol: An Old Drug With New Perspectives? Implication for Development of New Drugs. Issue 2 (2nd June 2016) - Cimini, Annamaria; d'Angelo, Michele; Benedetti, Elisabetta; D'Angelo, Barbara; Laurenti, Giulio; Antonosante, Andrea; Cristiano, Loredana; Di Mambro, Antonella; Barbarino, Marcella; Castelli, Vanessa; Cinque, Benedetta; Cifone, Maria Grazia; et al.
Abstract : Glioblastoma, the most common brain tumor, is characterized by high proliferation rate, invasion, angiogenesis, and chemo‐ and radio‐resistance. One of most remarkable feature of glioblastoma is the switch toward a glycolytic energetic metabolism that leads to high glucose uptake and consumption and a strong production of lactate. Activation of several oncogene pathways like Akt, c‐myc, and ras induces glycolysis and angiogenesis and acts to assure glycolysis prosecution, tumor proliferation, and resistance to therapy. Therefore, the high glycolytic flux depends on the overexpression of glycolysis‐related genes resulting in an overproduction of pyruvate and lactate. Metabolism of glioblastoma thus represents a key issue for cancer research. Flavopiridol is a synthetic flavonoid that inhibits a wide range of Cyclin‐dependent kinase, that has been demonstrate to inactivate glycogen phosphorylase, decreasing glucose availability for glycolysis. In this work the study of glucose metabolism upon flavopiridol treatment in the two different glioblastoma cell lines. The results obtained point towards an effect of flavopiridol in glycolytic cells, thus suggesting a possible new use of this compound or flavopiridol‐derived formulations in combination with anti‐proliferative agents in glioblastoma patients. J. Cell. Physiol. 232: 312–322, 2017. © 2016 Wiley Periodicals, Inc. Abstract : FLAP treatment affects glucose utilization pathways in two glioblastoma cell lines, bearing different PTEN status. The treatment strongly decreases the glycolytic enzymes with concomitant increase of cell death.